Deaf Students’ Perceptions of Career Guidance, Parental Social Support, and Career Planning at the Upper Secondary Education Level in Padang City - Torly Amora Jofipasi; Afdal Afdal; Rezki Hariko; Nurfarhanah Nurfarhanah; Fadilah Habibul Hasna; Resyelly Viona; Daharnis Daharnis (Program Studi Bimbingan dan Konseling Islam, 2026)
Career planning is a crucial stage in students’ career development, including for deaf students who face limited access to information and communication during the process of preparing to enter the workforce. To enable deaf students to plan their careers realistically and in line with their potential, adaptive career guidance and adequate social support from parents are essential. This study aims to describe perceptions regarding career guidance, perceptions regarding parental social support, and career planning. This study employs a quantitative approach with a descriptive design, involving 8 deaf students selected through saturation sampling. Data were analyzed using descriptive statistical techniques to obtain an overview of the trends of each variable. The results indicate that, overall, the findings show that deaf students have relatively positive perceptions of both career guidance and parental social support (from both fathers and mothers), which aligns with their level of career planning. This study underscores the importance of optimizing career guidance and parental involvement in supporting career planning readiness for deaf students. This study contributes to enriching the discussion on career guidance tailored to the needs of deaf students in their professional lives.